Implications of differences in safety and hygiene control practices for microbial safety and aflatoxin M1 in an emerging dairy chain: The case of Tanzania. (December 2020) - Ledo, James; Hettinga, Kasper A.; Kussaga, Jamal B.; Luning, Pieternel A.
Abstract: The varying performance of safety and hygiene control practices by chain actors can influence the consistent production of milk of good quality and safety in dairy chains. Therefore, the study aimed to investigate if differences in safety and hygiene control practices translate into distinctions in milk quality and safety at the farm, and to analyse the implications for actors further in the Tanzanian dairy chain. A previously developed diagnostic tool, customised for emerging dairy chains, was applied to assess and differentiate the performance of safety and hygiene control practices of actors from the farm to local retail shops. Based on interviews and on-site visits, each safety and hygiene control practice were differentiated into a poor, basic, intermediate or standard level. Milk samples were collected with a 7-day interval over three-time points to determine total bacterial counts (TBC), coliforms and Staphylococcus aureus . Besides, aflatoxin M1 (AFM1) occurrence was determined in farm milk as an indication of feed storage and monitoring practices. Data showed that none of the chain actors attained the standard level on any of the safety and hygiene control practices. Cluster analysis of on-farm safety and hygiene control practices generated two clusters, which differed mainly on the scores for udder and teat care, and disease detection practices. Differences in safety and hygiene control practices observed among farmers did not translate into differences in milk quality and safety. The analysis for AFM1 showed that 22% exceeded the maximum limit of the United States Food and Drug Authority Standard. Also, the microbial data showed that the farm milk already exceeded maximum limits of the East Africa Community (EAC) standard to the extent that no continued growth was observed further in the chain. The study demonstrates that improvements in milk quality and safety would require multiple practices to be upgraded to the standard level. Research is needed to advance the performance of control practices towards compliance with international standard requirements. Highlights: A previously developed customized assessment tool for emerging dairy chains was applied. Sub-standard performance typify safety and hygiene control practices along the chain. The majority of farm milk samples did not meet microbial criteria. Differences in sub-standard performance levels did not correlate with milk safety. Upgrading multiple practices to standard level is crucial for improving milk safety.